Maltol Improves APAP-Induced Hepatotoxicity by Inhibiting Oxidative Stress and Inflammation Response via NF-κB and PI3K/Akt Signal Pathways - Zi Wang; Weinan Hao; Junnan Hu; Xiaojie Mi; Ye Han; Shen Ren; Shuang Jiang; Yingping Wang; Xindian Li; Wei Li (MDPI AG, 2019)
Maltol, a food-flavoring agent and Maillard reaction product formed during the processing of red ginseng (Panax ginseng, C.A. Meyer), has been confirmed to exert a hepatoprotective effect in alcohol-induced oxidative damage in mice. However, its beneficial effects on acetaminophen (APAP)-induced hepatotoxicity and the related molecular mechanisms remain unclear. The purpose of this article was to investigate the protective effect and elucidate the mechanisms of action of maltol on APAP-induced liver injury in vivo. Maltol was administered orally at 50 and 100 mg/kg daily for seven consecutive days, then a single intraperitoneal injection of APAP (250 mg/kg) was performed after the final maltol administration. Liver function, oxidative indices, inflammatory factors—including serum alanine and aspartate aminotransferases (ALT and AST), tumor necrosis factor α (TNF-α), interleukin-1β (IL-1β), liver glutathione (GSH), superoxide dismutase (SOD), malondialdehyde (MDA), cytochrome P450 E1 (CYP2E1) and 4-hydroxynonenal (4-HNE) were measured. Results demonstrated that maltol possessed a protective effect on APAP-induced liver injury. Liver histological changes and Hoechst 33258 staining also provided strong evidence for the protective effect of maltol. Furthermore, a maltol supplement mitigated APAP-induced inflammatory responses by increasing phosphorylated nuclear factor-kappa B (NF-κB), inhibitor kappa B kinase α/β (IKKα/β), and NF-kappa-B inhibitor alpha (IκBα) in NF-κB signal pathways. Immunoblotting results showed that maltol pretreatment downregulated the protein expression levels of the B-cell-lymphoma-2 (Bcl-2) family and caspase and altered the phosphorylation of phosphatidylinositol 3-kinase/protein kinase B (PI3K/Akt) in a dose-dependent manner. In conclusion, our findings clearly demonstrate that maltol exerts a significant liver protection effect, which may partly be ascribed to its anti-inflammatory and anti-apoptotic action via regulation of the PI3K/Akt signaling pathway.